Plants on the Move: Hitch-Hiking With Ungulates Distributes Diaspores Across Landscapes - Baltzinger, Christophe; Karimi, Sorour; Shukla, Ushma (Frontiers in Ecology and Evolution, 2019)
This overview highlights the multiple pathways by which ungulates distribute diaspores across landscapes and over long distances. There are three primary and three secondary seed dispersal pathways where ungulate dispersal agents contribute to diaspore propagation, both with and without the intervention of other biotic (dung beetles) and abiotic (wind, gravity …) agents. These pathways may combine successive inter-dependent (diplochory) or totally isolated steps. Native, introduced and domestic ungulates co-occur in many ecosystems. They locally constitute diverse long-distance-vector assemblages for both native and exotic plants. However, ungulate taxonomic diversity conceals a much higher diversity in terms of the functional traits involved in ungulate-mediated dispersal: body morphology, body mass, feeding regime, digestive strategy, fur morphology, sociality, grooming behavior, habitat use. These traits may strongly affect one or more of the different phases in the dispersal loop (emigration, transfer and immigration), and consequently, impact the overall seed dispersal effectiveness, both quantitatively and qualitatively. In this study, we compare internal pathways, or endozoochory, where seeds have to survive digestive treatments (ingestion, ingestion and regurgitation), with external pathways, or epizoochory, where diaspores are carried on the outside of the vectors, including both primary epizoochory (direct adhesion to fur) and secondary epizoochory (diaspore-laden mud adhering to hooves or the body, transfer through contact with a conspecific). We further point out that it is not exceptional for diaspores from a given plant to be dispersed by a single vector through different processes, and for some to be moved through only a specific process but by a network of different vectors. Two parameters, however, remain obscure in this field of dispersal ecology: i) the relative proportion of all diaspores produced that are carried over long distances by large ungulates, and ii) the relative importance of ungulates on the whole as the main dispersal agent for plants. In a previous paper, we showed in particular that nearly half of the plants dispersed by fur-epizoochory did not feature any specific adaptations. We conclude by discussing methodological challenges and stressing research perspectives , like taking animal behavior and animal cognition into account, studying invasion of exotic plants and altitudinal plant dispersal.